Attentional bias in untreated panic disorder. - Reinecke, A; Cooper, M; Favaron, E; Massey-Chase, R; Harmer, C (2011)
The role of attentional biases in panic disorder has been well characterised. However, recent studies suggest an important effect of antidepressant and anxiolytic drugs on cognitive bias and most studies have included medicated patients in their sample. This study therefore examined cognitive bias in an untreated sample of participants with panic disorder (PD). A sample of 23 untreated participants with panic disorder with or without agoraphobia (PPD) and 22 healthy controls (HC) were tested with a Facial Expression Recognition task featuring different emotional intensities, a Faces Dot Probe task, a Self Beliefs task and an Emotional Stroop task. PPD showed exaggerated attentional biases to negative face and word stimuli in two different paradigms and endorsed more panic-related and negative self-attributions. They also showed enhanced perception of facial expressions of sadness. These tasks are sensitive to cognitive bias in a community-based sample of untreated PD participants. Attentional biases in panic disorder cannot be explained by the use of medication in this group and may therefore play a critical role in the underlying pathogenesis of the disorder.